Insights from using the Approaches to Studying as an Evaluation Tool for Educational Resource Development (Global Journal of Human-Social Science, 2013)
Over the past 12 years, an awareness of student characteristics has informed the design and interpretation of a series of research and evaluation studies in the Student Approaches to Learning (SAL) tradition. Instructors and developers of on-line learning objects have used the results to encourage active learning and implement better strategies. Addition of content learning items to the survey questions (along with evaluation questions and the 18-item ASSIST short form) made the questionnaire long enough to discourage completion. On some studies, two items ask about students' conceptions of-and motivations for learning have served as proxies for Approach scores, because they can be interpreted in the context of previous research. Non-conventional ways of analyzing the data have evolved because approaches are not evenly distributed. Significance tests based on assumptions of treatment groups, each randomly sampled from a population, are not always appropriate in real course settings.
Keywords: assist; approaches to studying; student learning; distance education; resident education; life science teaching; higher education; classroom assessmen